2010
DOI: 10.1007/s12291-010-0032-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Curcuma longa freeze dried rhizome powder with milk in STZ induced diabetic rats

Abstract: This study deals with the effects of freeze dried rhizome powder of Curcuma longa (C. longa) dissolved in milk on normal as well as diabetic models. Diabetes of type II and type I was within 3 days of a single administration of doses of 45 and 65 mg kg(-1) of streptozotocin respectively. Various parameters such as blood glucose levels, triglycerides, total cholesterol, high density lipoprotein, very low density lipoprotein, low density lipoprotein, serum glutamic oxaloacetic transaminase, serum glutamic pyruva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 28 publications
1
14
1
Order By: Relevance
“…The increased activity of this enzyme may be by either STZ- or hyperglycemia-induced tissue damage. Rai et al .,[23] reported an increase in ALP activity after induction of diabetes with STZ. In the present study, treatment with AECS and glibenclamide for 28 days showed a marked decrease in serum ALP activity.…”
Section: Discussionmentioning
confidence: 99%
“…The increased activity of this enzyme may be by either STZ- or hyperglycemia-induced tissue damage. Rai et al .,[23] reported an increase in ALP activity after induction of diabetes with STZ. In the present study, treatment with AECS and glibenclamide for 28 days showed a marked decrease in serum ALP activity.…”
Section: Discussionmentioning
confidence: 99%
“…EMC-1000 revealed significant reduction in serum creatinine and improvement in serum albumin and total protein level when compared with the diabetic animals sensitive lipases, which increase the lipolysis and releases more free fatty acids in the circulation. Increased fatty acid concentration also augments the b-oxidation of fatty acids, producing more acetyl-CoA, and cholesterol, which further enhances the development of atherosclerosis in DM [10,38,39]. Diabetic animals showed significant increase in the level of triglycerides, serum cholesterol, LDL cholesterol and decrease in HDL-cholesterol levels, while, administration of EMC demonstrated significant and dose dependant reduction in levels of serum triglyceride, serum cholesterol, LDL-cholesterol, and improvement in HDLcholesterol levels.…”
Section: Dyslipidemiamentioning
confidence: 99%
“…It is known that plant produce phytochemicals to protect itself, but recently, natural phytochemicals have gained a lot of attention as these phytochemicals have shown tremendous advantages to human health (Mehta et al 2010;Rai et al 2010a;Rai et al 2010b;Sharma et al 2009). Some of the well-known phytochemicals are flavonoids, phenolic compounds, lycopenes and carotenoids.…”
Section: Introductionmentioning
confidence: 99%